DETERMINATION OF CYTOPLASMIC MALE STERILE FACTORS IN ONION PLANTS ( ALLIUM CEPA L.) OF VNIISSOK'S BREEDING - T.P. Suprunova; A.N. Logunov; V.V. Logunova; A.F. Agafonov (Овощи России, 2011)
Molecular markers were used for screening of the onion plants of VNIISSOK's breeding for cytoplasmic male sterility. Allelic variations of the mitochondrial genes orfА501 and cob were reveled among studied onion samples. Use of the PCR-markers for these genes allowed identifying the cytoplasmic types of 14 onion genotypes. Application of these molecular markers in breeding program could help to select genotypes wit certain type of cytoplasm and may be useful for high throughput identification of cytoplasmic male sterile factors in large onion breeding populations.